1987
DOI: 10.1108/eb026803
|View full text |Cite
|
Sign up to set email alerts
|

Nearest Neighbour Searching in Binary Search Trees: Simulation of a Multiprocessor System

Abstract: This paper describes the simulation of a nearest neighbour searching algorithm for document retrieval using a pool of microprocessors. The documents in a database are organised in a multi‐dimensional binary search tree, and the algorithm identifies the nearest neighbour for a query by a backtracking search of this tree. Three techniques are described which allow parallel searching of the tree. A PASCAL‐based, general purpose simulation system is used to simulate these techniques, using a pool of Transputer‐lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, there have been attempts to extend techniques for informational retrieval to multiprocessor architectures [16,26,28,371. Stewart and Willett [36], for example, describe three techniques that allow parallel searching of k -cl trees. Their results support the use of multiprocessor systems for searching applications in information retrieval.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been attempts to extend techniques for informational retrieval to multiprocessor architectures [16,26,28,371. Stewart and Willett [36], for example, describe three techniques that allow parallel searching of k -cl trees. Their results support the use of multiprocessor systems for searching applications in information retrieval.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One way of computing the similarity between a document and the query is to count the number of terms in common between them; the documents presented to the user first are those that contain the greatest number of terms specified in the query. The best-match searching procedure in such ranked output retrieval systems identifies the terms in common between the query and each of the documents in the file [36]. In molecular biology, to gain information about a newly sequenced protein, biologists compare the protein's amino acid sequence against those of many known proteins, searching for ones with very similar sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Vector Processing. Stewart and Willett [80] describe an algorithm for nearest neighbour search using a multi-dimensional binary search tree, using networked …”
Section: Other Approachesmentioning
confidence: 99%
“…Given the variety of approaches in this section we will not attempt to describe the interaction between architecture, the algorithms and the types of query parallelism used. [80] described an algorithm for nearest neighbour search using a multi-dimensional binary search tree, using networked microprocessors. Documents are represented by vectors, as is the query: the vector contains identifiers of terms in that document.…”
Section: Other Approachesmentioning
confidence: 99%
“…Work in Sheffield over the last few years has considered the use of SIMD architectures for text retrieval [8,33], and the availability of transputers provided an opportunity to investigate the potential of MIMD parallelism for this application. Stewart and Willett have recently reported a simulation study of the implementation of a binary-tree based nearest neighbour searching algorithm for document databases on a transputer system [39]. The simulation demonstrated that there was substantial scope for increasing the speed of searching but that the precise degree of speed-up was crucially dependent upon the way in which the parallelism in the searching task was implemented, and upon the characteristics of the documents.…”
Section: Introductionmentioning
confidence: 99%